ANALISIS NOVEL SITI NURBAYA KARYA MARAH RUSLI - Erlina Erlina (Ensiklopedia Research and Community Service Review, 2026)
This  research  aims  to  analyze  the  intrinsic  elements  that  constitute  the novel Siti   Nurbaya by   Marah   Rusli.   This   novel   is   a   phenomenal   classic Indonesian  literary  work  that  addresses  crucial  issues  regarding  the  clash between love and traditional Minangkabau customs. The research method employed is descriptive qualitative with a structural literary approach. The analysis results indicate that the main theme, which is a tragedy of love hindered by customs, characterization that represents the conflict between modernity and traditionalism, and a systematic progressive plot, serve as the foundation for building the novel's narrative. This research concludes that Siti Nurbaya is not merely a romance story but a strong social critique of the rigidity of customs at that time.Keywords: Siti Nurbaya, Marah Rusli, Intrinsic Elements, Custom Critique, Classic Literature